2011
DOI: 10.1021/la202990y
|View full text |Cite
|
Sign up to set email alerts
|

Control of the PEO Chain Conformation on Nanoparticles by Adsorption of PEO-block-Poly(l-lysine) Copolymers and Its Significance on Colloidal Stability and Protein Repellency

Abstract: The physical adsorption of PEO(n)-b-PLL(m) copolymers onto silica nanoparticles and the related properties of poly(ethylene oxide) (PEO)-coated particles were studied as a function of the block copolymer composition. Copolymers adopt an anchor-buoy conformation at the particle surface owing to a preferential affinity of poly(L-lysine) (PLL) blocks with the silica surface over PEO blocks when a large excess of copolymer is used. The interdistance between PEO chains at particle surface is highly dependent on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 68 publications
0
37
0
Order By: Relevance
“…It can be deduced by comparing the Flory radius (R F ) of surface chains, 5,7 to either the distance between PEG grafting points (D), or the thickness of the PEG layer (L). It can be deduced by comparing the Flory radius (R F ) of surface chains, 5,7 to either the distance between PEG grafting points (D), or the thickness of the PEG layer (L).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be deduced by comparing the Flory radius (R F ) of surface chains, 5,7 to either the distance between PEG grafting points (D), or the thickness of the PEG layer (L). It can be deduced by comparing the Flory radius (R F ) of surface chains, 5,7 to either the distance between PEG grafting points (D), or the thickness of the PEG layer (L).…”
Section: Resultsmentioning
confidence: 99%
“…3, bottom row). 5,7,52 As all nanoparticles are nearly electrostatically neutral under the conditions used for ITC, the enthalpic driving force is attributed to a combination of weak non-covalent forces such hydrogen bonding and/or van der Waals interactions, rather than electrostatic effects. Human serum albumin (HSA) is the most abundant protein in plasma, known for its extraordinary ligand-binding capacity, its capability as a biomarker, and used clinically to treat a number of diseases.…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding distance between two PEG 5000 chains was d PEG =2.6 nm. The PEG chains conformation can be deduced by comparing the distance d PEG to the Flory radius of PEG in good solvent (R F = 6.1 nm), as already done by Louguet et al (30). The distance d PEG being smaller than R F , suggests that the PEG chains strongly interact with each other and were forced to stretch away from the surface of micelle adopting a brush conformation.…”
Section: Influence Of the Process On The Structure Of Nanoparticlesmentioning
confidence: 99%
“…It has been demonstrated that a stretching of a polymeric chain produce a blue shift of the SPR, due to the decrease of ligand density in the vicinity of the AuNP [37]. It is also known that a high density of SH-PEG grafted on the AuNPs surface lead to a change of conformation from mushroom to brush [36,38,39]. Thus, the observed blue shift is likely to be caused by a stretching of the SH-PEG chains, induced at high grafting densities of SH-PEG.…”
Section: Resultsmentioning
confidence: 99%